2016
DOI: 10.1002/dev.21412
|View full text |Cite
|
Sign up to set email alerts
|

Associations between respiratory arrhythmia and fundamental frequency of spontaneous crying in preterm and term infants at term‐equivalent age

Abstract: This study investigated whether lower vagal function in preterm infants is associated with increased fundamental frequency (F 0; frequency of vocal fold vibration) of their spontaneous cries. We assessed respiratory sinus arrhythmia (RSA) during quiet sleep as a measure of vagal function, and its relationship with the F 0 of spontaneous cries in healthy preterm and term infants at term‐equivalent age. The results showed that preterm infants have significantly lower RSA, and higher overall F 0 than term infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 63 publications
(108 reference statements)
4
20
0
Order By: Relevance
“…Our research group also showed that shorter gestational age is significantly associated with higher F 0 , regardless of body size at cry recording and intrauterine growth retardation [IUGR]. Thus, rather than being a product of a smaller body size, the increased F 0 of spontaneous cries in preterm infants may be the result of more complicated neurophysiological states, such as low vagal activity ( Shinya et al, 2016 ), due to their different intra- and extrauterine experiences.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Our research group also showed that shorter gestational age is significantly associated with higher F 0 , regardless of body size at cry recording and intrauterine growth retardation [IUGR]. Thus, rather than being a product of a smaller body size, the increased F 0 of spontaneous cries in preterm infants may be the result of more complicated neurophysiological states, such as low vagal activity ( Shinya et al, 2016 ), due to their different intra- and extrauterine experiences.…”
Section: Introductionmentioning
confidence: 77%
“…The present study included 77 preterm infants (gestational age < 37 weeks) and 30 term infants (gestational age ≥ 37 weeks) who were recruited between 2011 and 2015 from Kyoto University Hospital. The preterm infants were assigned to two subgroups according to gestational age: very preterm (VP) infants (gestational age < 32 weeks; n = 36) and moderate-to-late preterm (MLP) infants (gestational age ≥ 32 weeks but < 37 weeks; n = 41); all participants were included in previous studies conducted by our research group (i.e., the preterm group in Shinya et al, 2014 , 2016 and the term group in Shinya et al, 2016 ). The exclusion criteria consisted of severe neurological complications such as brain lesions (including periventricular leukomalacia, and Grade III or IV intraventricular hemorrhages), chromosomal abnormalities, and/or medical treatment required for respiratory disease at term-equivalent age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research using RSA methods have shown that healthy vagal tone is associated with human social engagement and selfregulation (Geisler et al, 2013), including the capacity for sympathy among children (Taylor et al, 2015) and compassionate responses toward others' suffering (Stellar et al, 2015). Poor vagal tone is associated with health problems including preterm, high-risk infants (Shinya et al, 2016), and anxiety disorders in adults (Chalmers et al, 2014), including military combat veterans with post-traumatic stress disorder (PTSD) Modified from Lenfesty and Fikes (2017b) after Porges (2011). (Jovanovic et al, 2009) and victims of childhood abuse and neglect (Dale et al, 2009).…”
Section: The Human Autonomic Nervous System (Ans) and The Polyvagal Tmentioning
confidence: 99%
“…Impaired VNA innervation may be responsible for decreased cardiac baroreflex’s (BRS) control of heart rate in premature compared to term infants [ 54 ]. Abnormalities in neuro- and socioemotional development observed in premature and autistic children may also reflect lower VNA; estimates of VNA have been used as a marker of infant development [ 51 , 52 , 55 ].…”
Section: Introductionmentioning
confidence: 99%